A prospective study of multimodal cocktail intercostal injection for chest pain relief after costal cartilage harvest for rhinoplasty. Issue 6 (July 2022) - Dong, Wenfang; Wang, Xin; Wang, Huan; You, Jianjun; Zheng, Ruobing; Xu, Yihao; Zhang, Xulong; Guo, Junsheng; Fan, Fei
Abstract: Our aim was to evaluate the efficacy and safety of multimodal cocktail intercostal injection for the relief of chest pain after costal cartilage harvest for rhinoplasty. Consecutive patients who underwent costal cartilage harvest during rhinoplasty were prospectively assigned as per patient preference to group A (injection containing ropivacaine, parecoxib sodium, epinephrine, and compound betamethasone), group B (intercostal nerve block (ICNB)), or group C (ICNB plus patient-controlled analgesia (PCA)). The outcomes were visual analogue scale (VAS) scores for chest pain after costal cartilage harvest, rescue analgesia, complications, and cost during the first two days. Of the 66 patients assessed, 63 (29 patients in group A, 13 in group B, and 21 in group C) were eligible and included. The VAS scores in group A were significantly lower than those in groups B and C (all p<0.001). Group A had a significantly lower rate of rescue analgesia due to a VAS score of more than 4 (3.45%, 1/29) compared with group B (46.15%, 6/13; p=0.001) and group C (28.57%, 6/21; p=0.012). Complications were observed only in group C (nausea/vomiting 28.57%; dizziness/headache 23.81%), which differed significantly from group A (p=0.002 and 0.006, respectively). The mean cost for group A (US $15 (0)) was significantly lower than it was for group C (US $113.1 (4.4), p<0.05), but higher than it was for group B (US $5.97 (0), p = -). Multimodal cocktail intercostal injection may be superior for chest pain relief after costal cartilage harvest for rhinoplasty compared with ICNB with or without PCA. Further study is warranted.